Prevalence of Subclinical Optic Nerve Changes in Patients With Chronic Otitis Media: A Prospective Observational Study - Abdullah Naeem Syed, Muhammad Firdous, Rehan Moinuddin Shaikh, Ahsan Qureshi, Shafqat Hussain, Muhammad Asad Chughtai, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic otitis media (COM) is traditionally considered a localized inflammatory disease of the middle ear; however, chronic inflammation and cholesteatoma-related destruction may extend toward neuro-ophthalmic structures. Emerging evidence suggests that subtle optic nerve involvement may occur silently, yet remains under-recognized in routine clinical practice. Objective: To determine the prevalence of subclinical optic nerve changes in patients with chronic otitis media using optical coherence tomography (OCT) and visual evoked potentials (VEP), and to identify associated risk factors. Methods: This prospective observational study was conducted at Al-Shifa Trust Eye Hospital, Rawalpindi, and Mughal Eye Hospital, Lahore, from January 2022 to February 2023. A total of 90 adults with clinically confirmed COM underwent comprehensive ophthalmic evaluation, including RNFL and GCC measurements using spectral-domain OCT and P100 latency/amplitude assessment through VEP. Subclinical optic nerve change was defined as structural thinning or abnormal VEP responses without visual symptoms. Associations with COM type, laterality, and disease duration were analyzed. Results: Subclinical optic nerve involvement was identified in 27 patients (30%). Optic nerve changes were significantly more common in unsafe COM (57.1%) compared with safe COM (17.7%) (p < 0.001). Patients with disease duration >2 years (44.7%) and bilateral COM (42.1%) demonstrated higher prevalence compared with shorter-duration (19.0%) and unilateral cases (21.1%) (p < 0.05). OCT revealed significant RNFL and GCC thinning, particularly in temporal and inferior quadrants, while VEP showed markedly prolonged P100 latency. Conclusion: A substantial proportion of COM patients exhibit silent optic nerve alterations. Early OCT and VEP screening, especially in unsafe or long-standing COM, may prevent progression to clinically significant optic neuropathy. Keywords: Chronic otitis media, optic nerve, subclinical neuropathy, OCT, VEP, RNFL thinning, cholesteatoma.